PERAMALAN JUMLAH PERMOHONAN PASPOR : SYSTEMIC LITERATURE REVIEW - Wibowo, Besar Tri; Vita Nurul Fathya; Okky Pratama Martadireja (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The mobility of society, influenced by globalization, continues to increase, with fewer limitations on travel distances. People around the world can travel to other countries easily and quickly. Cross-border movement requires a travel document in the form of a passport as an individual's identification when entering and leaving a country. The number of passport applications varies each year. Typically, public interest in obtaining a passport rises during certain seasons, such as the Hajj season or long holidays. To anticipate uncertainties in passport application numbers, this study aims to explore which forecasting methods can be used to predict the number of passport applications within a specific timeframe. This research employs a survey approach by reviewing scientific journals or articles published between 2020 and 2025. Through this study, we can identify the types of methods used in similar research. Based on the findings, the most commonly used approach is the Autoregressive Integrated Moving Average (ARIMA), while the approach with the highest research accuracy is the Fuzzy Time Series Model Cheng, achieving an accuracy of 99.55%.